2003
DOI: 10.1111/j.1532-5415.2004.52023.x
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Mechanisms of Impaired Visceral Pain Perception in Older People

Abstract: There is increasing recognition that aging can have a profound effect on the presentation of illness. Older patients with diseases of visceral organs are much more likely than younger adults to present atypically. Examples are the frequent absence of pain in older patients with conditions such as myocardial infarction, peptic ulcer disease, and pneumothorax. Recent developments have helped elucidate the complex processes involved in signaling information from the effects of noxious stimuli on visceral organs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 30 publications
(56 reference statements)
0
26
0
Order By: Relevance
“…22 Aging influences the perception of thermal and noxious stimuli in different dimensions (e.g., pain in the cutaneous tissues, deep tissues, and viscera) and various mechanisms may underlie these differences. 9,27,36 CHEPs are integrated responses to contact heat stimulation at the skin; hence, differences in the pattern of skin innervation may underlie the effect of age. The abundance of skin innervation, particularly of free nerve endings in the epidermis, can be demonstrated with neural markers, 20,24 including protein gene product 9.5, calcitonin generelated peptide, and substance P. 13 Our group and others have previously shown that skin innervation is reduced with age in both upper and lower limbs, and there is a linear decline in epidermal innervation with age.…”
Section: Discussionmentioning
confidence: 99%
“…22 Aging influences the perception of thermal and noxious stimuli in different dimensions (e.g., pain in the cutaneous tissues, deep tissues, and viscera) and various mechanisms may underlie these differences. 9,27,36 CHEPs are integrated responses to contact heat stimulation at the skin; hence, differences in the pattern of skin innervation may underlie the effect of age. The abundance of skin innervation, particularly of free nerve endings in the epidermis, can be demonstrated with neural markers, 20,24 including protein gene product 9.5, calcitonin generelated peptide, and substance P. 13 Our group and others have previously shown that skin innervation is reduced with age in both upper and lower limbs, and there is a linear decline in epidermal innervation with age.…”
Section: Discussionmentioning
confidence: 99%
“…13 Many studies have focused on the age-related pain threshold changes. [18][19][20][21][22][23][24][25] The majority of these studies suggests that there is an increase in pain perception threshold, but most of the work has been methodologically weak. 26 Moreover, age differences in pain may be dependent on the pain sale used.…”
Section: Physiological Changesmentioning
confidence: 99%
“…However, in the present study, we found that there was no relationship between LDA and symptoms. In relation to the mechanism of impaired perception of visceral pain in elderly people, Moore and associates [49] pointed out that some age-related differences do in fact exist.…”
Section: Discussionmentioning
confidence: 99%